Atrial Fibrillation Should Guide Prophylactic Tricuspid Procedures During Left Ventricular Assist Device Implantation. Issue 5 (September 2018) - Anwer, Lucman A.; Tchantchaleishvili, Vakhtang; Poddi, Salvatore; Daly, Richard C.; Joyce, Lyle D.; Kushwaha, Sudhir S.; Topilsky, Yan; Stulak, John M.; Maltais, Simon
Abstract : Atrial fibrillation (AF) and tricuspid regurgitation (TR) are common in patients undergoing left ventricular assist device (LVAD) implantation. TR progression is associated with the presence of AF, and questions remain as to who benefits from tricuspid valve procedures (TVPs). We examined the impact of preoperative AF on TR progression after LVAD implantation. From February 2007 to May 2014, 250 patients underwent LVAD implantation at our institution. Patients with concomitant TVP were excluded from this analysis (113 patients). The indication for LVAD was destination therapy in 80 patients (58%) and the etiology of heart failure was ischemic in 73 (53%). Follow-up was available in all early survivors for a total of 393 patient-years of support. Of the 137 non-TVP patients, 52 (38%) had AF preoperatively. Observed overall survival at 1, 3, and 5 years was 82%, 67%, and 55%, respectively. Median grade of TR increased from 2 preoperatively to 3 ( p = 0.04) in the AF group and 2.2 ( p = 0.75) in the non-AF group at 5 years of follow-up. We also observed a significant difference in the degree of TR between groups at 3 months ( p = 0.03) and 12 months ( p = 0.01) postimplantation, and a trend toward significance at 18 ( p = 0.06) and 24 ( p = 0.07) months. The presence of AF is associated with early progression of TR after LVAD implantation. Addition of concomitant TVP in patients with preoperative AF may be considered in patients with less than severe TR. The impact of these findings on right ventricular failure/remodeling remains to be evaluated.